The Role of Knowledge Sharing and Learning Orientation in Improving Innovative Work Behavior among Millennials in Indonesia - Palumian, Yonathan; Gunawan, Kristian Alvin; Tarigan, Zeplin Jiwa Husada; Umbara, Aang Noviana (Petra International Journal of Business Studies, 2021)
Millennials in Indonesia are now perceived as the main actor of the future generation in the country. As Indonesia is approaching the demographic benefit in 2030-2020, they are expected to innovate in all industrial sectors to support the nationwide development. The purpose of this study is to conduct a prediction on innovative work behavior based on knowledge sharing and learning orientation among millennial workers in Indonesia. This research was conducted under a quantitative approach with a questionnaire-based survey involving 246 millennial respondents working in several sectors. Using partial least square, the finding of this explanatory research implies that learning orientation does have no significant influence on innovative work behavior. However, knowledge sharing has a significant effect on innovative work behavior among Indonesian millennials at the workplace.